PENINGKATAN KUALITAS PELAYANAN PUBLIK MELALUI PENILAIAN KEPATUHAN TERHADAP STANDAR PELAYANAN SESUAI UNDANG UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK Studi Di Dinas Kesehatan Kota Salatiga Tahun 2016-2017 - Cahyanti, Anifah Putri; Setiyono, Budi; Adnan, Muhammad (Journal of Politic and Government Studies, 2018)
The fulfillment of public service standards as regulated in the Constitution Number 25 Year 2009 is an obligation for any service executant. Not every public service executant, whether they are in the ministry/institution or local governments, has implemented what the consitituion has regulated. The results of compliance assessment on the service standards which is done by Ombudsman, Central Java representatives in 2016 at the Health Agency of Salatiga City indicates that the fulfillment of public service standards at the agency is still at the unsatisfactory level (red zone). At the 2017 the results improved, even not significantly, at the intermediate level (Yellow Zone). This is where the questions arise; Can the compliance assessment implemented by Ombudsman improve the quality of public services at all? This research applies mix method, which combines the qualitative and quantitative methods using the collected data from interviews, observations, and questionnaires. Some source triangulations is implemented to test the data validity by comparing the results of interviews to the results of questionnaires which are addressed to the civilians as the service users. Based on the research results, compliance assessment implemented by Ombudsman at the Health Agency of The Salatiga City could not yet improve the quality of public services held by OPD. This is discovered from surveys on the society’s satisfaction on the service: the service at 2016-2017 was still poor, This was caused by the service executant who didn’t implement the constitution number 25 year 2009 and yet to understand the indicators included in the public service. Compliance assessment that is expected to give transparency to the society so the civilans don’t have to ask when they use the service hasn’t alse succeeded yet, this is because the society tend to ask to the officers rather than look for the information. Keywords: Ombudsman, Public Service, Compliance Assessment